ANALGOSEDATION IN THE EMERGENCY DEPARTMENT: CURRENT GUIDELINES AND CLINICAL PRACTICE COMPREHENSIVE REVIEW - Aleksandra Soltys; Katarzyna Anna Borzęcka; Agnieszka Szwed; Daria Aleksandra Warzocha-Żurek; Ewa Maria Polewczak-Karp; Katarzyna Wawrzonek; Krystian Andryszko; Marcelina Dymon; Natalia Ziemba-Furgała; Paulina Krysa (International Journal of Innovative Technologies in Social Science, 2026)
This article discusses the use of procedural sedation and analgesia (PSA) in the Emergency Department (ED), with an emphasis on ensuring patient safety and comfort during brief medical procedures. The aim of this study is to present the principles of sedation use, its organization, indications, monitoring methods, and potential complications, as well as to emphasize the need for standardized management in the ED.The methodology is based on a review of available guidelines, classifications (including the ASA system), sedation assessment scales, and an analysis of the pharmacological properties of the most commonly used medications, such as ketamine, propofol, midazolam, fentanyl, and etomidate. Data on patient monitoring and the organization of the clinical workflow are also included.The results indicate that appropriate selection of sedation levels and medications, as well as close monitoring of vital signs, significantly impacts procedural safety. An individualized approach is crucial, especially in high-risk patient groups (children, the elderly, and trauma patients). The use of combination therapy and alternative techniques, such as nerve blocks, can reduce adverse effects.The conclusions emphasize the need to implement standards, staff training, and protocols in the ED. Properly performed procedural sedation increases treatment effectiveness, minimizes the risk of complications, and improves patient comfort.